Ventral midline incisional Richter's hernia: A case report. (March 2022) - Ndong, Abdourahmane; Tendeng, Jacques Noel; Diallo, Adja Coumba; Diao, Mohamed Lamine; Nyemb, Philippe Manyacka Ma; Konaté, Ibrahima
Abstract: Background: Richter hernia is a particular entity characterized by partial strangulation of the intestinal wall through an hernial orifice. This form is associated with high morbidity and mortality due to the high risk of necrosis followed by intestinal perforation. We report a rare Case of Richter type strangulated incisional hernia. Case: It was a 68-year-old patient with a history of 7 pregnancies including two deliveries with cesarean section by midline laparotomy. She had an abdominal pain evolving for 48 hours with vomiting and cessation of passage of flatus and stool. Physical examination revealed a midline laparotomy scar with a painful non-reducible periumbilical mass. Surgical exploration via a 5 cm midline incision above the mass revealed an hernial sac, the opening of which revealed ventral midline incisional Richter's hernia with bowel necrosis. Bowel resection followed by end-to-end anastomosis and primary suture repair were done. The postoperative course was uneventful. Conclusion: Our observation shows that the high risk of intestinal necrosis should lead to a rapid diagnosis in order to reduce postoperative morbidity. The treatment without mesh seems to be a safe option in the context of emergency and intestinal resection. Highlights: Richter hernia is a particular entity associated with high morbidity and mortality. There is a high risk of necrosis followed by intestinal perforation. Pure tissue repair seems to be a safe option in a context of intestinal resection.